STUDI PENINGGALAN ARSITEKTUR ISLAM MANDAR DI KECAMATAN BANGGAE KABUPATEN MAJENE - samad, nurmiati (Al-Hikmah, 2019)
Architectural heritage of Islam in Pambo 'borang District of Banggae Majene has existed long ago but the history of the architectural Islamic beginning has not widely known by the public. To find out through interviews with community leaders and literature studies. Islamic architecture is the art of building that maintains the Islamic concept in terms of shape, appearance and function of the building it self. This research a prof. of first spread of study Islam on Mandar that must be known by the public widely to make strengthen the historical evidence of this village’s civilization. A Netherland researcher has ever come to Pambo'borang village for examining the history of Pambo’ boring’s empire civilization that is familiar and know from a historical museum in the Netherlands. But the indigenous people of this village have not been clearly communicated about the historical fact in Pambo'borang’s village.